PREVALENCE OF BACTERIOBILIA IN PATIENTS UNDERGOING ELECTIVE COLECYSTECTOMY - Rafael Soares de OLIVEIRA1; Paula da SILVA; Carlos Alfredo Salci QUEIROZ; Juverson Alves TERRA-JÚNIOR; Eduardo CREMA (ABCD: Arquivos Brasileiros de Cirurgia Digestiva, 2018)
ABSTRACT Background: Cholelithiasis is one of the diseases with greater surgical indication. Currently, laparoscopic cholecystectomy is the gold standard in the treatment of cholelithiasis. Aim: To analyze the culture of bile from patients with cholelithiasis, mainly in the occurrence of brown and mixed stones. Methods: Was carried out a prospective study with 246 cases with biliary lithiasis who underwent elective laparoscopic cholecystectomy. Bile culture was performed in all. During anesthetic induction the patients received a single dose of intravenous cefazolin 1 g. At the end of the surgery, the gallbladder was punctured, its contents extracted and immediately placed in a sterile 20 ml propylene flask and promptly sent to bacterioscopy with Maconkey and blood agars. Incubation at 37° C for 24 h was carried out. A protocol was elaborated to include the main factors potentially related to cholelithiasis and the possible presence of associated bacterial infection. Results: Of the 246 patients, 201 had negative bile culture and 45 positive. Of the 45 patients with bacteriobilia, 34 had growth of a single type of bacterium in bile culture and 11 more than one. Conclusions: It was observed a relationship between bacteriobilia and age, suggesting that age is a risk factor for bacteriobilia. The use of antibiotic prophylaxis in the elderly is therefore recommended.